Variability in drug use among newborns admitted to NICUs: a proposal for a European multicentre study - Laura Cuzzolin (Journal of Pediatric and Neonatal Individualized Medicine, 2014)
The use of drugs in newborns admitted to NICUs is characterized by a great variability. This widespread phenomenon, observed both within and between different countries, has been highlighted by reporting data on the treatment of neonatal sepsis and PDA throughout Europe: the dosages and the intervals between administrations of ciprofloxacin and fluconazole varied significantly and a wide variation was also observed as regards the use of NSAIDs to treat PDA. Given the unique characteristics of the neonatal population, the use of drugs on an individual basis could be sometimes justified. However, other factors such as the lack of evidence-based guidelines and the common use of drugs in an off-label manner (more than 80% of newborns receive this kind of treatment) could contribute to the variability in medicine use, making the neonatal population vulnerable to adverse drug reactions (ADRs) and medication errors: the potential ADRs rate, 3 times higher in pediatric wards, is more significantly higher in NICUs and the frequency of medication errors (mostly dose errors) widely exceeds the medium value. The differences in clinical practices observed between NICUs need to be addressed at a European level and a multicentre study could be useful to harmonize drug use in newborns.